Impact company size and audit opinion on audit report lag (empirical study of manufacturing companies listed on the Indonesia stock exchange in 2016–2019) - Kamilia Zahrani; Rachma Isna Dhiar Cahya Prasetya; Rika Jayanti; Khairunnisah (Institute of Computer Science (IOCS), 2023)
This research examines the effect of company size and the previous year's audit opinion on audit report lag with KAP's reputation as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016–2019. This type of research is quantitative, using secondary data taken through the IDX website. Determination of the sample in this study using a purposive sampling method, with a full selection of 136 manufacturing companies. The data analysis technique uses multiple linear regression tests using SPSS version 23 software. The results show that partially the company size and the previous year's audit opinion significantly affects audit report lag. The KAP reputation strengthens the relationship between the company size and the previous year's audit opinion with audit report lag in manufacturing companies for the 2016–2019 period.